2017
DOI: 10.1021/acs.est.7b04346
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Primary Emissions and Photochemical Formation of Isocyanic Acid Downwind of Oil Sands Operations

Abstract: Isocyanic acid (HNCO) is a known toxic species and yet the relative importance of primary and secondary sources to regional HNCO and population exposure remains unclear. Off-road diesel fuel combustion has previously been suggested to be an important regional source of HNCO, which implies that major industrial facilities such as the oil sands (OS), which consume large quantities of diesel fuel, can be sources of HNCO. The OS emissions of nontraditional toxic species such as HNCO have not been assessed. Here, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…In ambient measurements, HNCO correlated with markers of vehicle exhaust including benzene, toluene, and black carbon (BC). 30,72 Further, from the diurnal cycle observed in HNCO measurements in Toronto, two separate sources for HNCO were identied based on time of day. 30 First, concentrations of HNCO generally increased each morning due to morning rush hour traffic.…”
Section: Fossil Fuel Combustionmentioning
confidence: 99%
See 4 more Smart Citations
“…In ambient measurements, HNCO correlated with markers of vehicle exhaust including benzene, toluene, and black carbon (BC). 30,72 Further, from the diurnal cycle observed in HNCO measurements in Toronto, two separate sources for HNCO were identied based on time of day. 30 First, concentrations of HNCO generally increased each morning due to morning rush hour traffic.…”
Section: Fossil Fuel Combustionmentioning
confidence: 99%
“…These values agree closely to the values obtained for diesel vehicles in Wentzell et al (2013) 30 and gasoline vehicles in Brady et al, 33 but much lower than dynamometer measurements by Suarez-Bertoa et al, 37 Link et al, 34 and Jathar et al 35 Further evidence of summer and winter emission differences are provided by Suarez-Bertoa et al who found that on average in their eet (both gasoline and diesel vehicles) that vehicles operated at À7 C had emission ratios more than four times greater than when operated at 23 C. 37 In the second mobile study, Liggio et al conducted a regional aircra study in the Athabasca oil sands in northern Alberta, Canada, where bitumen deposits are extracted and rened to crude oil resulting in heavy industrial activity. 72 In the study, HNCO was measured using a time-of-ight CIMS over 22 ights. Elevated HNCO concentrations were attributed to diesel exhaust through correlation with black carbon levels.…”
Section: Fossil Fuel Combustionmentioning
confidence: 99%
See 3 more Smart Citations